2020
DOI: 10.1049/enc2.12011
|View full text |Cite
|
Sign up to set email alerts
|

Energy management and economic analysis of multiple energy storage systems in solar PV/PEMFC hybrid power systems

Abstract: This study proposes an energy management system (EMS) to manage a standalone hybrid power system (HPS) comprising solar photovoltaic (PV), proton exchange membrane fuel cell (PEMFC), and a battery energy storage. The battery and a hydrogen storage system in PEMFC provide short-and long-term electricity storage, respectively. The EMS ensures electrical efficiency during normal/abnormal operation of the HPS and related limitations, namely unexpected variations in solar irradiance and loads, PEMFC cold start, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…For the second question, existing methods are mainly used for optimising the entire power network (e.g. a microgrid) [6,7] or hybrid systems [8] with renewables, including PV and ESS, as well as other resources, which cannot be directly applied to the power bidding problem. A recent study [9] reported a data-driven method for energy bidding in the electricity market; however, this method was designed for a microgrid, not for the case in this study.…”
Section: Xumentioning
confidence: 99%
“…For the second question, existing methods are mainly used for optimising the entire power network (e.g. a microgrid) [6,7] or hybrid systems [8] with renewables, including PV and ESS, as well as other resources, which cannot be directly applied to the power bidding problem. A recent study [9] reported a data-driven method for energy bidding in the electricity market; however, this method was designed for a microgrid, not for the case in this study.…”
Section: Xumentioning
confidence: 99%
“…Constraint (7) ensures that the device cannot be both moving and parking; Constraint (8) ensures that the arrival and departure places are consistent with the parking place; Constraint (9) ensures that the device cannot be both arriving and departing at the same time and place; Constraint (10) ensures that the moving variable is consistent with the departure variable; Constraints (11) and (12) ensure that the arrival variable is consistent with the moving variable; and Constraint (13) represents the travel-time constraint.…”
Section: Transportation System Modelmentioning
confidence: 99%
“…MBESS scheduling is complicated owing to complex spatiotemporal characteristics and uncertainties of different systems and environments, such as transportation congestion, electricity price volatility [5], renewable energy fluctuations [6], and energy storage systems [7]. Inconsistent movement and charge‐discharge frequencies as well as system uncertainty modelling are the two main difficulties of the MBESS problem [8, 9].…”
Section: Introductionmentioning
confidence: 99%